Home and Sexuality : The 'Other' Side of the Kitchen - Scicluna, Rachael M. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
"Scicluna's richly ethnographic study of older lesbians' experiences of kitchens [...] takes the reader through the intricacies of the politics of gender relations and sexuality by focusing on a key domestic space in which they are played out, and sometimes fought out, on a daily basis." -Sarah Green, University of Helsinki, Finland "The scrupulous attention to detail and emergent analysis reveal that the taken for granted has powerful potential for exposing hitherto hidden political, personal issues." -Judith Okely, University of Oxford, UK "This 'back story' of lesbian life has been missing from studies of political and social organizing [and is] a very welcome addition to the growing literature on daily life, material culture, and aging." -Ellen Lewin, University of Iowa, USA.
Keywords: sociologie rodiny -- Velká Británie; lesbické ženy -- Velká Británie; sociology of family -- Great Britain; lesbians -- Great Britain; elektronické knihy; monografie; electronic books; monographs